Implementation of Two-point Quadrature Gauss-Legendre Method on 2D Gravity Anomaly Modeling in Basins with Density Distribution Varied Polynomially as a Function of Depth - Wahyu Srigutomo; Sesri Santurima; Cahyo Aji Hapsoro; Hairil Anwar; I Gede Putu Fadjar Soerya Djaja (Jurnal Geofisika, 2018)
Study of basin geometry basin is important in geosciences and geophysical exploration. Gravity method can be used to address this issue by measuring gravity anomalies on the surface caused by density contrast between the bedrock and the sediment that fills the basin, geometry of the basin and surface topography. Numerically, gravity anomaly modeling can be conducted using two-point rule Gauss-Legendre Quadrature method, for a case where density contrast varies with depth exponentially. Within the scope of this study, gravity anomalies on the surface are significantly affected by the geometry of the curvature of the bedrock as well as the topographic elevation of the surface and the selected density contrast, and are not significantly affected by the undulation of the bedrock curvature.